Estrategias empresariales - Perdomo Paredes, Sandra; Molina Peralta, Iraide; Lanza, Laura Camila; Hurtatis Leal, Miller (Sello Editorial UNAD, 2024)
This book is the product of research work called “Estrategias Empresariales para la Asoción de Mujeres Rurales de Colombia y el Caqueta (ASMUCOCA)” (Business Strategies for the Association of Colombia’s and Caqueta’s Rural Women - ASMUCOCA - in English), which has two chapters, the first of which addresses topics such as: Business strategy and the solidarity economy, in which it is explained what business strategies are; business strategies in the solidarity economy; and the significance of planning in the business strategies of solidarity economy’s organizations. It also refers to the ASMUCOCA case study, which is carried out under the methodology of strategic planning.